STUDI LITERATUR REVIEW : ANALISIS BAHAYA PENGGUNAAN PESTISIDA TERHADAP KESELAMATAN DAN KESEHATAN KERJA PARA PETANI - Nurlyani Malau (CV. Adiba Aisha Amira, 2023)
Pesticides “are largely characterized as toxic preparations that are used to control intruders that harm people. In the health aspect, pesticides are a significant tool. Mainly used to prevent people from disease vectors, either directly or indirectly, from certain bodies. This research plans to dissect and analyze various records that examine medical conditions that occur in shepherds due to resistance to pesticides. The test strategy used was a recorded survey with optional data obtained from the Science and Innovation Record (SINTA), Google Researcher, PubMed Focal and Sciencedirect information files with a span of 10 years. As a result, 15 objective posts were analyzed. The findings show that most of the farmers use pesticides to control plant hoppers. Overuse and without the use of human defense equipment can result in pesticides passing on to shepherds. Drug exposure can cause various health problems, including anemia, high blood pressure, diabetes mellitus, nervous system problems, hypothyroidism and reproductive problems in women, and fertility problems in men. Exposure to pesticides can also cause tremors and other physical health problems such as skin irritation, dizziness, nausea, coughing up phlegm, headaches and difficulty breathing.